2022
DOI: 10.3390/pharmaceutics15010124
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Antibiotic Potency Improvement of Levofloxacin by Producing New Salts with 2,6- and 3,5-Dihydroxybenzoic Acid and Their Comprehensive Structural Study

Abstract: Recently, solid-state engineering has become a promising approach to improving the stability and potency of antibiotics. Levofloxacin (LF) is a broad-spectrum fluoroquinolone antibiotic marketed in solid and solution dosage forms. However, this substance forms solid hydrates under ambient conditions and degrades due to lighting, which may change its solid properties and dose. In addition, resistance cases have been reported due to long-time antibiotic usage. This research aims to allow LF to react with antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Both ionic and non-ionic reactions of the fluoroquinolone group, i.e., ciprofloxacin and levofloxacin, with some substituents increase the solubility of these compounds [6,9], as well as showing increased stability towards humidity and light, which is the main advantage of these systems. For example, the combination of levofloxacin-citric acid [6] and levofloxacin-dihydroxybenzoic acid [7], and ciprofloxacin with cyclodextrin and cucurbit (7)-uril (CB7) improves photostability up to three-fold [27].…”
Section: Antibiotic Multi-component Structure Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Both ionic and non-ionic reactions of the fluoroquinolone group, i.e., ciprofloxacin and levofloxacin, with some substituents increase the solubility of these compounds [6,9], as well as showing increased stability towards humidity and light, which is the main advantage of these systems. For example, the combination of levofloxacin-citric acid [6] and levofloxacin-dihydroxybenzoic acid [7], and ciprofloxacin with cyclodextrin and cucurbit (7)-uril (CB7) improves photostability up to three-fold [27].…”
Section: Antibiotic Multi-component Structure Developmentmentioning
confidence: 99%
“…One of the common strategies is reacting antibiotics with inorganic chemicals (metals/halogens) or organic compounds, such as other drugs, excipients, nutraceuticals, etc. Moreover, in addition to improving the solid characteristics, experiments have shown that fluoroquinolone antibiotics can enhance potency by changing the polarity and penetrability of the bacteria's membrane through non-covalent reactions [6,7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations